THE BALINESE WOMEN’S POLITICAL PARTICIPATION IN THE GENERAL ELECTIONS CONDUCTED FROM 1997 TO 2004 (IN THE PERSPECTIVE OF CULTURAL STUDIES) - Rahayu, Luh Riniti; Putra Astiti, Tjok. Istri; Suastika, I Made; Parimartha, I Gde (E-Journal of Cultural Studies, 2011)
This study discusses the Balinese women’s political participation in thegeneral elections conducted in 1997, 1999 and 2004. During these years, in spiteof being supported by reformation, there was a gap with regard to the Balinesewomen’s participation in politics, which was assumed to result from numerousfactors. Therefore, the problems formulated in this study are (1) how the Balinesewomen politically participated in the general elections conducted in 1997, 1999and 2004; (2) what factors affected their political participation in the generalelections conducted in 1997, 1999 and 2004?; (3) what were the effects andmeanings of their political participation in the general election conducted in 1997,1999 and 2004 viewed from the values of equality in gender? Qualitative methodwith multidisciplinary approach from the perspective of cultural studies wasadopted in this study. Several critical social theories were employed forsharpening the analysis.The results of the study show that the Balinese women’s politicalparticipation in the general election conducted in 1997 was 11.11%; that therecruitment system still referred to the concepts applied in the New Order, that is,through the women’s organizations established by the government with highnepotism. While their political participation in the general election conducted in1999 decreased by 1.62% as a consequence of reformation, in the general electionconducted in 2004 it rose by 7.27%, resulting from the changes in the generalelection regulations. The factors which encouraged the Balinese women toparticipate in politics were that they were influenced by the men who werepoliticians and close to them such as their husbands and fathers, the women’smovements and the general election regulations. As far as the domestic domain isconcerned, their political participation was positive. What is meant is that theywere able to acquire asymmetric relation of power; however, negatively, they hadmultiple responsibilities resulting from the multiple roles they played. In thepolitical domain, they were dominated by men; in addition, their politicalparticipation gave the meanings of equality, being constitutional and beingprestigious.